Childhood obesity and overweight prevalence trends in Portugal – COSI 2008 and 2010 - Rito, Ana Isabel (2012)
INTRODUCTION: Previous data indicated that the estimated prevalence of childhood overweight and obesity was above 30%, being Portugal one of the European countries with the highest prevalence. OBJECTIVE: The purpose of this study was to monitor trends in childhood overweight and obesity in Portugal, based on the first and second data collection (2008 and 2010) from the National Nutritional Surveillance System - COSI Portugal. METHODS. Specific prevalence of overweight and obesity was determined, using 2 different diagnostic criteria from the first and second data collection (2008 and 2010) of the National Nutritional Surveillance System - COSI Portugal - among the seven geographic regions. The survey is affiliated with the World Health Organization European Childhood Obesity Surveillance Initiative and followed a standardized methodological protocol. 3765 children (6-8 years old) were enrolled from 181 schools in 2008 and 4020 children from 172 schools in 2010 (national representative samples). Height and weight were directly measured by trained fieldworkers. Overweight (including obesity) and obesity prevalence were calculated using the international body mass index cut-offs according to CDC and IOTF criteria. RESULTS: According to IOTF criteria the mean crude prevalence of overweight decreased from 28,1% (2008) to 26,5% (2010) (p=0,49), and childhood obesity varied from 8,9% (2008) to 9,1% (2010). With the CDC criteria we found that the prevalence of overweight and obesity varied from 32,3% and 14,6% in 2008 to 30,3% and 14,2% in 2010. Gender differences have remained relatively stable from 2008-2010, according to IOTF criteria, i.e. the prevalence of overweight was significantly higher in boys (30,0%-2008 and 26,8%-2010) than in girls (26,1%-2008 and 25,8%-2010). CONCLUSION: Overall we observed that the prevalence of overweight decreased suggesting that childhood overweight and obesity in Portugal might be leveling off. However, these results reinforce that Portugal continues to be, consistently, one of the countries with the highest magnitude of childhood obesity and that the reference used to define it is important, since it provides different estimates.